Business Process Analysis at RSIA Lombok Dua-Dua Pharmacy Using the Deming Cycle Method - Kartika, Dhian Satria Yudha; Fitri, Anindo Saka; Purwitasari, Astri; Firlyandita, Marsyanda; Sugiarto, Sugiarto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The quality of public service is an important factor that must be considered. This study evaluates the business processes of the RSIA Lombok Dua-Dua Pharmacy using the PDCA (Plan-Do-Check-Act) cycle approach to improve the quality of pharmacy operations. The purpose of this study is to analyze operational processes, identify key constraints, and develop solutions to improve the efficiency and quality of pharmacy services. This study compares several studies related to business process analysis in a service. The comparison results obtained the completeness of the methods used and applied to the case study. The business process of this study is considered more comprehensive than previous studies. Data collection methods include observation, interviews, and documentation. The main problems identified include long waiting times, lack of adequate digital devices, and limited additional facilities. The analysis process uses the Fishbone diagram and the Five Whys method to determine the root cause of the problem. This study provides solutions including the adoption of digital technology systems, workflow optimization, and facility improvements as well as staff training. The evaluation results show opportunities to improve operational efficiency has increased by 85% from the previous 75% and service quality through the implementation of continuous improvement, in terms of time there is an increase in waiting time to 15 minutes from the previous 30 minutes. The PDCA method is able to provide a strong foundation for decision making in developing pharmacy services, to create a better health environment for the community.